Validation of High-Performance Liquid Chromatography for determination and stability assessment of dobutamine hydrochloride in pediatric intravenous therapy - Calegari , Tatiany (2024)
Severely ill children and newborns typically require a wide range of intravenous medications as part of specific therapies tailored to their developmental and growth characteristics. Intravenous medications for pediatric patients are dosed based on their weight and body surface area, and their response to drug therapy varies with age. Many drugs are originally developed for adults but are prescribed to children based on clinical experience and scientific publications, considering the severity of the condition. In this context, one such medication widely used in pediatric treatment since the 1970s is dobutamine hydrochloride, an inotropic drug with some vasodilatory effect. We aimed to validate High-Performance Liquid Chromatography to determine the concentration and stability of dobutamine hydrochloride. The dobutamine hydrochloride (250mg/ 2mL of water) was used as the sample. The parameters of analytical performance determined were selectivity, linearity, range, precision, accuracy, robustness and stability. The developed method has proved to be selective; linear in the range from 80% to 120% of the theoretical test concentration; precise in repeatability and intermediate precision; exact at the concentrations of 0.40, 0.50 and 0.60 mg/mL; robust with drug variations proportional to the deliberate changes caused in the composition and flow rate of MF, and column temperature; and stable for 24 hours after sample preparation. The High-Performance Liquid Chromatography analytical methodology for dobutamine hydrochloride was considered validated according to Resolution 899/2003 of the Brazilian Health Regulatory Agency (Anvisa).